A study on effectiveness of Sodium Dichloroisocyanurate (NaDCC) as surface water purifier: Aquatab tablet - Haziqah, Mimi; MAT DAUD, AZRA MUNIRAH (Recent Trends in Civil Engineering and Built Environment, 2022)
Sodium dichloroisocyanurate (NaDCC) is a chemical that can be used to purify water. Purification of water is intended to improve the quality of water that is both harmless and safe for human consumption. Sodium dichloroisocyanurate (NaDCC), which is frequently used in emergencies, is a chlorine alternative that may have some advantages over household-based interventions in developing countries. NaDCC is a white crystalline powder or granular substance that has a faint chlorine odor. A typical effective concentration of free available chlorine (FAC) in drinking water is around 1 mg/L. Assuming a daily water intake of 2 L per person, the daily NaDCC intake would be 3 mg. A product that form NaDCC will be Aquatab tablet for treat surface water. The guideline values for water quality were determined using the National Research on Lakes Water Quality (NAHRIM). The study location will be at G3 lake in the campus of Universiti Tun Hussein Onn Malaysia. The Aquatab tablet product that contain NaDCC will be determine the effectiveness as water purifier and identify the active element NaDCC in this studies. To quantify NaDCC's efficacy in terms of total dissolved solids (TDS), turbidity (NTU), pH, electrical conductivity, and oxidation reduction potential.